2012
DOI: 10.3747/pdi.2010.00208
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Nursing Experience is Beneficial for Lowering the Peritonitis Rate in Patients on Peritoneal Dialysis

Abstract: ♦ Objectives: We explored the relationship between the experience level of nurses and the peritonitis risk in peritoneal dialysis (PD) patients. ♦ Methods: Our observational cohort study followed 305 incident PD patients until a first episode of peritonitis, death, or censoring. Patients were divided into 3 groups according to the work experience in general medicine of their nursesthat is, least experience (<10 years), moderate experience (10 to <15 years), and advanced experience (≥15 years).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…Theoretically, more experienced nurse trainers should provide more efficient training with good communication and counselling skills, and demonstrate greater sensitivity to patients' physiological and psychological challenges. This tenet is supported by a single-centre, Chinese observational cohort study of 305 incident PD patients [32] (Table 2), which found that patients trained by nurses with more than 15 years of general medical experience had a lower risk of Gram-positive peritonitis compared with patients trained by nurses with between 10 and 15 years' experience [adjusted hazard ratio (HR) 2.69, 95% CI: 1.03-6.98; P = 0.04] or less than 10 years' experience (HR 3.16, 95%CI: 1.20-8.30; P = 0.02). In contrast, another single-centre retrospective study by Chow et al [33] in Hong Kong (Table 2), including 200 PD patients, reported an inverse association between the duration of a PD trainer's experience and peritonitis rates.…”
Section: Who Should Provide Pd Training?mentioning
confidence: 88%
“…Theoretically, more experienced nurse trainers should provide more efficient training with good communication and counselling skills, and demonstrate greater sensitivity to patients' physiological and psychological challenges. This tenet is supported by a single-centre, Chinese observational cohort study of 305 incident PD patients [32] (Table 2), which found that patients trained by nurses with more than 15 years of general medical experience had a lower risk of Gram-positive peritonitis compared with patients trained by nurses with between 10 and 15 years' experience [adjusted hazard ratio (HR) 2.69, 95% CI: 1.03-6.98; P = 0.04] or less than 10 years' experience (HR 3.16, 95%CI: 1.20-8.30; P = 0.02). In contrast, another single-centre retrospective study by Chow et al [33] in Hong Kong (Table 2), including 200 PD patients, reported an inverse association between the duration of a PD trainer's experience and peritonitis rates.…”
Section: Who Should Provide Pd Training?mentioning
confidence: 88%
“…() reported that 255 of 655 patients (38.9%) experienced more than one episode of peritonitis between 2000–2012. In China, a single‐centre study in Beijing reported that 129 first episodes of peritonitis occurred among 305 patients (42.2%) (Yang, Xu, Zhuo, & Dong, ). A study in Guangzhou found that 309 of 1117 patients (27.7%) presented with a first episode of peritonitis (Fan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However there are few published data on the optimal nurse-to-patient ratios or training protocols (76). It is difficult to define "appropriate qualification and experience," and there is conflicting evidence regarding the relation between nursing experience and clinical outcome (77,78).…”
Section: Training Programsmentioning
confidence: 99%